Electricity Harvesting From Water Vapour Using Chitosan Film - Jalil, Aiizat Ikhwan Abdul (2020)
The depletion of world petroleum, gas and coal reserves has led to the growth of a greater consensus on excessive fossil energy sources that have caused environmental problems such as the greenhouse effect and climate change. In the context of maintaining sustainable energy improvement, renewable energy sources offer several benefits compared to fossil energy such as eco-friendly, sustainable and zero greenhouse effect. The availability of renewable energy sources for electrical generation is the wind, biomass, solar, geothermal, water, etc. Even so, the overall potential from renewable energy sources is quite significant and has not been utilised optimally. Hence, a new application of chitosan film has been successfully generating electrical energy from water vapour exposure. Chitosan was fabricated in film form by using solution casting method whereby manufactured from the waste product of crustacean shells. Chitosan has unique characteristics such as good biocompatibility, excellent film-forming ability, biodegradation, non-toxicity and hydrophilicity, which can be used in many applications. The presence of amine in chemical structure adores interacting with water molecules or any analytes whereby chitosan becomes prominent in the energy materials field. Therefore, the preliminary study on the laboratory testing of chitosan film to harvest water vapour which represented as relative humidity (RH) in range of 30% - 90% at variance 20 °C – 35 °C temperatures was done. The results showed the generation of electrical energy was started to increase and to reach an almost steady state when exposed to ≥78% RH at various temperatures. As a result of the highest exposure at 90% RH, 4% chitosan film yield the highest electrical energy of 123.50 μW at 35 °C for 24 hours. This verified that the harvesting process through direct chemical interaction between amine groups (NH2) on chitosan film and water vapour molecules (H2O) generating electrical energy which proved by the FTIR result. Thereafter the evidence from the harvesting process, a functionality test was conducted by using water flow setup which a representative of the actual model water streams under a long period of time. The functionality test results exhibited the electrical energy of chitosan films have a similar trend with the previous characterization whereby the highest electrical energy of 118.89 μW was yielded by 4% chitosan for 30 weeks while the longest was exhibited from 4.5% with 33 weeks yet the electrical energy was lower than 4%. The material characterization proved a greater amount of agglomeration on chitosan film higher than 4%, which effecting electrical pathway yet create a stronger chemical bond. The optimum amount of RH and temperatures can be used for future work in water vapour panel to increase the electrical energy harvesting amount. Furthermore, the electrical energy from water vapour panel can be applied in electrical devices.